Effects of hybrid maturity and growth stage on yield and composition of forage and grain sorghums when harvested as silage - J. Dickerson; R. Smith; K. Bolsen; T. Walter (Kansas Agricultural Experiment Station Research Reports, 1985)
Thirteen sorghum hybrids chosen to represent a range of sorghum types were evaluated in two separate trials. Each was harvested at three stages of grain development: milk to early-dough, late-dough, and hard-grain. Among the forage sorghums, there was a 26-day range in days to half bloom from early to late maturing varieties. Harvest date did not affect crude protein content. However, whole-plant DM yield was significantly lower at the last harvest for the three latest maturing varieties. Grain yield increased over time in the early and intermediate hybrids. Lodging increased significantly over time for all varieties except DeKalb FS-25E. Among the grain sorghums, there was only a 4-day range in days to half bloom and very little difference in plant height. The forage sorghum was later maturing and taller. Whole-plant DM yields for the grain sorghums were highest at late-dough. Grain yields and grain to forage ratios generally increased with maturity, except when there were losses due to birds. Grain sorghums started to lodge by the hard-grain stage.
Keywords: Cattlemen& #x27; s Day; 1985; Kansas Agricultural Experiment Station contribution; no. 85-319-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 470; Beef; Maturity; Growth stage; Yield; Forage; Grain sorghum; Silage